UKRAINIAN NEOPATRIMONIAL BUREAUCRACY AND THE DISTRIBUTION OF ECONOMIC BENEFITS DURING THE WAR - Avksentiev, Anton (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
This study examines the distribution of economic benefits in the interests of the neopatrimonial bureaucracy amid the Russo-Ukrainian war. It argues that the neopatrimonial theory provides a more accurate explanation of the functioning of Ukraine’s political regime during wartime, as binary oppositions such as "democracy vs. totalitarianism" fail to adequately describe the actual exercise of power. Neopatrimonial bureaucracy is understood as the dominant politico-administrative class that exploits its political status and official position for personal enrichment. The paper analyzes two key aspects of economic benefit distribution – official budgetary revenues and "rent-seeking" mechanisms. Based on empirical analysis, the study finds that the influence of the neopatrimonial bureaucracy has strengthened in both of these areas. It demonstrates the rise in official budget expenditures allocated to sustain the neopatrimonial bureaucracy and reveals how the incomes of its representatives significantly exceed the national average. The study systematizes 15 primary "rent-seeking" instruments used by various sectoral fractions of the neopatrimonial bureaucracy to generate profits. The research highlights that the full-scale war has not led to a rejection of the rent-seeking model. On the contrary, it has provided neopatrimonial bureaucrats with new rent-seeking opportunities. Most of these instruments are directly linked to the war, particularly in the areas of defense procurement, reconstruction, humanitarian aid, fortifications, mobilization, and border crossing. However, some highly profitable rent-seeking mechanisms during wartime are not directly related to the war (for example in the banking sector) but have become feasible due to additional state restrictions and regulations. Drawing on sociological research, the paper argues that beyond economic losses for the broader society, the rent-seeking behavior of the neopatrimonial bureaucracy leads to a decline in public trust in state institutions and government bodies.